High-Fat Diet Changes Hippocampal Apolipoprotein E (ApoE) in a Genotype- and Carbohydrate-Dependent Manner in Mice - Lane-Donovan, Courtney (PLoS One, 2016)
Alzheimer’s disease is a currently incurable neurodegenerative disease affecting millions of individuals worldwide. Risk factors for Alzheimer’s disease include genetic risk factors, such as possession of ε4 allele of apolipoprotein E (ApoE4) over the risk-neutral ApoE3 allele, and lifestyle risk factors, such as diet and exercise. The intersection of these two sources of disease risk is not well understood. We investigated the impact of diet on ApoE levels by feeding wildtype, ApoE3, and ApoE4 targeted replacement (TR) mice with chow, high-fat, or ketogenic (high-fat, very-low-carbohydrate) diets. We found that high-fat diet affected both plasma and hippocampal levels of ApoE in an isoform-dependent manner, with high-fat diet causing a surprising reduction of hippocampal ApoE levels in ApoE3 TR mice. Conversely, the ketogenic diet had no effect on hippocampal ApoE. Our findings suggest that the use of dietary interventions to slow the progression AD should take ApoE genotype into consideration.